2019
DOI: 10.1111/pops.12627
|View full text |Cite
|
Sign up to set email alerts
|

The Ideological Foundations of Economic Protectionism: Authoritarianism, Social Dominance Orientation, and the Moderating Role of Political Involvement

Abstract: Even though economic globalization and foreign trade are major topics in the political discourse of most societies and negative attitudes toward international trade are prevalent, there is a lack of research investigating the ideological roots of protectionist preferences from a psychological perspective. In the present research, we examined the implications of right‐wing authoritarianism (RWA) and social dominance orientation (SDO) for trade attitudes. Using data from two nationally representative samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Using data from the American National Election Studies from 2000 to 2008, Johnston (2013) finds that authoritarian values are the most consistent indicator of individuals' support for import restrictions across all years and models. In Germany, Jedinger and Burger (2020) find that authoritarian values correlate with support for restrictions on foreign trade, controlling for a wide range of other factors.…”
Section: Introductionmentioning
confidence: 83%
“…Using data from the American National Election Studies from 2000 to 2008, Johnston (2013) finds that authoritarian values are the most consistent indicator of individuals' support for import restrictions across all years and models. In Germany, Jedinger and Burger (2020) find that authoritarian values correlate with support for restrictions on foreign trade, controlling for a wide range of other factors.…”
Section: Introductionmentioning
confidence: 83%
“…In light of this mixed evidence about the role of material self-interest, other authors argue that noneconomic factors such as cultural concerns, identity, ideology, or concerns about sovereignty are much more important drivers of the globalization backlash than material concerns. For example, opposition to economic globalization is stronger among individuals holding right-wing authoritarian, nationalist, and isolationist values and attitudes ( Jedinger & Burger 2020, Mansfield & Mutz 2013) and among those concerned about the negative sociotropic effects of trade (Mansfield & Mutz 2009). Opposition to political and sociocultural globalization is related to concerns about restrictions on national sovereignty (Ecker-Ehrhardt 2014) and a cultural backlash against mainstream culture and neoliberalism (Hopkin & Blyth 2019, Norris & Inglehart 2019.…”
Section: Materials or Nonmaterials Causes?mentioning
confidence: 99%
“…Other work suggests that populist radical right parties have greater electoral potential when a higher percentage of immigration opponents hold more redistributive economic views in a protection-based attitude package (Pardos-Prado 2015; see also Cochrane 2013;Gidron and Ziblatt 2019;Lefkofridi and Michel 2017;Webb and Bale 2014). Jedinger and Burger (2019) found that economic protectionism -a part of traditional left-wing platforms -correlates positively with right wing authoritarianism (Altemeyer 1996), an individual difference that reflects cultural traditionalism and authoritarian intolerance. Carmines, Ensley, and Wagner (2016) found that Republicans with a protection-based attitude package were the most likely to support Donald Trump during the 2016 primaries.…”
Section: The Role Of Ideological Attitudesmentioning
confidence: 99%